Analysis Of Quality Service Toward Revisiting Intention To The Pediatric Outpatient Clinic At RSUD Belitung Timur With Customer Satisfaction As The Intervening Variable - Primasari Jalil, Vonny; Supriyantoro, Supriyantoro; Aida, Mus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2022)
Health services at the hospital is one of the objectives of the quality of services that will also affect the return of patients to the hospital if patient satisfaction has been felt and the quality of service received by patients well. Understanding the health status and needs of public health services and educating the public about health services and involving the community in providing effective health services are the basis of health service providers. The purpose of this study was to analyze the effect of service quality on the intention to revisit outpatients in Pediatric hospitals in East Belitung Hospital with customer satisfaction as an intervening variable. This type of research is quantitative research, with analytic descriptive using cross-sectional study approaches. The number of samples in this study were 200 people. Data collection was carried out using a questionnaire instrument. Analysis using Structural Equation Modeling (SEM) is also known as Analysis of Moment Structures (AMOS). The results of the study are that service quality has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on return visits, and customer satisfaction has a positive and significant effect on return visits. Keywords: Service Quality, Customer Satisfaction, and Returning Intentions